PENGARUH LATIHAN REAKSI DAN AKSELERASI TERHADAP KECEPATAN LARI 100 METER PADA SISWA YANG MENGIKUTI EKSTRAKURIKULER ATLETIK YAYASAN AL-MARWA KOTA PEKANBARU - Fauzan Paris Purba; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations and monitoring that the authors have done for students who participate in the athletic extracurricular foundation al marwa kota pekanbaru on a 100 meter sprint performed by students, there are still very striking problems, namely: Less maximal when doing speed when running there are still shortcomings when doing movement on a 100 meter sprint is probably due to the lack of training for students. This research was conducted on the football field in Tassel (TOR). This research was conducted from January to July 2019. With the implementation of 3 meetings per week. While the pre-test and post-test were performed before the exercise and after the reaction and acceleration exercise. To overcome these problems, some exercises were given so that students could perform better in competition in the future, and especially after a reaction training and student acceleration more than before to keep track of your opponents and achieve maximum performance in the future. The design of this study was a pre-test post-test one group design that was started with a 40-meter Pree test run test. The sample then received a response training program and accelerated during 16 meetings. The Posttest test then carried out a 40-meter sprint. Based on the results of the pre-test and post-test data analysis, the t-test resulted in a T-count of 2.017 and Ttable 2.015. It means that Thitung> Ttable can be summarized as follows: There is a significant influence between reaction training and acceleration (X) with a running speed of 100 meters (Y) Students who take the athletic extracurricular foundation al marwa kota pekanbaru.Key Words: Reaction And Acceleration, Speed